An Organization Development Intervention on Perceived Organization Support, Supervisor Feedback Environment, Supervisory Communication and Trust to Improve Supervisor-Subordinate Relationships: An Action Research Study in a Dessert Café and Restaurant, Phi Phi Island, Thailand - Phunthasaen, Ananya; Chungviwatanant, Sming (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This research investigates the impact of Organization Development Intervention (ODI) on Perceived Organization Support (POS), Supervisor Feedback Environment, Supervisory Communication, and Trust to increase the level of Supervisor- Subordinate Relationships, conducted in a small sized dessert café-restaurant on Phi Phi Island, Krabi province, Thailand. Nine Organization development interventions (ODIs) were implemented over a five month period from January-May, 2019 and conducted with 18 participants, who are the store supervisors and operation staffs of the dessert café-restaurant in this study. Both quantitative (survey questionnaire) and qualitative (observation and in-depth interview) methods were used in the process of collecting and analyzing data in this study. The research was conducted using the concept of action research. The findings indicated that (1) There are differences between the Pre and Post organization development interventions (ODIs) on Perceived Organization Support (POS), Supervisor Feedback Environment, Supervisory Communication, Trust and Supervisor- Subordinate Relationships; and (2) Perceived Organization Support (POS), Supervisor Feedback Environment, Supervisory Communication, Trust and Supervisor- Subordinate Relationships showed statistically significant increases after ODI.